Spectroscopic analysis of C80 doping with group III and group V elements using semiempirical PM3 molecular modelling technique - Ibrahim, Medhat; ElHaes, Hanan; Hameed, Ali Jameel; Essa, Ali Hashem (Eclética Química, 2008)
Semiempirical calculations at the level of PM3 of theory were carried out to study the structural and electronic properties of C80 and some of its doped derivatives with the elements of group III and V at the level of PM3 of theory. We have selected these elements to be substituted in the fullerene-C80 cage in order to show the effect of such structural change on the electronic properties of the molecules studied. The theoretical IR spectra, some of physical and chemical properties of the molecules studied are obtained and discussed.